2018
DOI: 10.1177/0017896918782279
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behaviours and sedentary lifestyle prevention among young Mexicans: A pilot study

Abstract: Objective: To evaluate the effects of a universal prevention programme for disordered eating behaviours (DEB) and sedentary lifestyle among Mexican young people. Design: Non-experimental single group field study with repeated measures (pre-test, post-test and at 6-month follow-up). Setting: Public high school in Hidalgo, Mexico. Methods: In all, 214 young women and 154 young men aged 15–18 years with a mean age of 16.4 participated in the study. For both young women and men, data were collected using the Brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
2
9
2
5
Order By: Relevance
“…Rodriguez-Ventura et al ( 2018) reported only a statistically significant (p < 0.05) decrease in the time spent watching TV. Saucedo-Molina et al (2018) reported a statistically significant (p < 0.05) increase in PA in the total sample. However, such an increase was higher among boys.…”
Section: Physical Activity and Sedentary Behaviours Outcomesmentioning
confidence: 84%
See 1 more Smart Citation
“…Rodriguez-Ventura et al ( 2018) reported only a statistically significant (p < 0.05) decrease in the time spent watching TV. Saucedo-Molina et al (2018) reported a statistically significant (p < 0.05) increase in PA in the total sample. However, such an increase was higher among boys.…”
Section: Physical Activity and Sedentary Behaviours Outcomesmentioning
confidence: 84%
“…2 Map from the origin of the included interventions Carrete, 2018;Cruz-Bello et al, 2019;Elizondo-Montemayor et al, 2014;Perichart-Perera et al, 2008;Polo-Oteyza et al, 2017;Vazquez et al, 2017). But some studies (5/13) reported significant reductions in BMI (Rodriguez-Ventura et al, 2018;Saucedo-Molina et al, 2018;Zacarias et al, 2019) or obesity prevalence (Balas-Nakash et al, 2010;Rios-Cortazar et al, 2013). Caballero-Garcia et al (2017) was the only multi-site study (carried out in four different states of Mexico) and found that anthropometric changes varied depending on the site.…”
Section: Changes In Anthropometric Outcomesmentioning
confidence: 99%
“…En cuanto al riesgo de TCA, el porcentaje aquí encontrado (9.3%) es mayor a lo reportado en un estudios previos, uno llevado a cabo en el estado de Jalisco (7.3%) (27) y otro en el estado de Hidalgo (5.6%) (28), así como en otros lugares de la república mexicana (29,30), por lo que la evidencia apunta a un incremento de esta psicopatología alimentaria a través del tiempo.…”
Section: Discussionunclassified
“…Diseño: no experimental, transversal de tipo prospectivo y con un alcance correlacional (21). Muestreo y tamaño de muestra: el muestreo fue no probabilístico de tipo intencional por disponibilidad.…”
Section: Materiales Y Métodosunclassified
“…Se implementó un programa de educación nutricional y actividad física llamado PECANSS (Prevención de conductas alimentarias no saludables y sedentarismo), el cual fue diseñado en el año 2013 por un equipo multidisciplinario (nutriólogos, psicólogos, diseñador gráfico y preparador físico certificado). Este ha sido probado en muestras de adolescentes, hombres y mujeres, donde se obtuvieron resultados positivos 24 , por lo que se decidió retomarlo en esta investigación. Se hizo una adaptación para los profesores, en la que se modificaron los requerimientos nutricionales, las recomendaciones de AF y parte del lenguaje utilizado; posterior a esto se renombró como PECANSS V2.0 (Prevención de conductas alimentarias no saludables y sedentarismo, versión dos), empleando todo el material visual y didáctico sobre conceptos básicos de alimentación y nutrición, así como diseños de menús saludables.…”
Section: Intervención Nutricionalunclassified